Analisis Time Cost Trade Off sebagai Strategi Percepatan Proyek untuk Efisiensi Pembangunan Gedung Laboratorium Teknik 4 Institut Teknologi Sumatera - Septi, Fadillah Tri; Sari, Dian Perwita (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
Project delays in construction are complex issues that have a significant impact on increasing costs and completion time. This study aims to analyze the optimal project acceleration strategy for the construction of the Engineering Laboratory Building (GLT) 4 at ITERA, which is experiencing delays, by applying the Time Cost Trade Off (TCTO) method. This quantitative research compares three alternative acceleration strategies: adding working hours (overtime), adding work shifts, and adding labor and heavy equipment. Primary data was obtained through interviews with the contractor, while secondary data included the time schedule, the Budget Plan (RAB), and other project documents. The analysis was conducted by compiling a critical work network, calculating normal duration and costs, and analyzing the crash duration and crash cost for each alternative. The results show that the project's normal condition has a duration of 224 days with a total cost of Rp 16,927,594,301. All three acceleration strategies proved effective in reducing both duration and cost. The strategy of adding labor and heavy equipment proved to be the most optimal, resulting in a duration of 163 days (time efficiency of 27.23%) with the highest cost efficiency of 5.75%. The alternative of adding work shifts resulted in the fastest duration of 161 days (time efficiency of 28.13%), but with lower cost efficiency (4.92%). Meanwhile, adding overtime hours was the weakest alternative with a duration of 178 days (time efficiency of 20.54%) and a cost efficiency of 3.51%. The research confirms that adding resources (labor and equipment) provides the most beneficial time-cost trade-off for this project, where the indirect cost savings from shortening the heavy equipment rental period are greater than the additional direct costs.